VARIASI PERTUMBUHAN TINGGI PADA UJI KLON Eucalyptus pellita F. Muell. DI WONOGIRI, JAWA TENGAH - Sri Sunarti (Jurnal Pemuliaan Tanaman Hutan, 2012)
Nine clones of Eucalyptus pellita F. Muell propagated from selected plus trees in the first-generation seedling seed orchard were tested together with a control of seedling in a clonal test established at Wonogiri, Central Java. The design of clonal test was Randomized Complete Block, which was laid-out as single treeplot of 16 replications with spacing of 3 m x 2 m. Measurements of tree height were conducted at age 12 months. There were significant differences between the clones in height growth. All tested clones showed better tree height than the control of seedling with superiority ranging from 42% to165%. Almost all clones also showed better performance than their original population of the first-generation seedling seed orchard. Clone repeatability for height at age 12 months was 0.90, while individual repeatability for height was 0.38. The top three clones were clones 1 and 3  which propagated from selected plus trees in first generation seedling seed orchard and clone 2 which is selected tree in border of A. mangium seed orchard.